Measuring E-Service Quality through Village SIAP Application: The Success Key of Public Information Services in Bojonegoro - Zirly Ika Putri; Ana Kumalasari; Musta’ana; Yunes Mohammed Muthanna Al-Murisi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Village SIAP application designed to support public services at the village level still faces problems that are not optimal due to incomplete and inaccurate data. This study aims to determine the success of implementing the Village SIAP application by assessing the quality of electronic services using the D&M Model. In this edition, information, systems, and services become three dimensions to determine the quality of IS services, namely Information Quality (INFQ), System Quality (SYSQ), and Service Quality (SERQ). The type of research used is descriptive qualitative research. This study involved in-depth interviews with government officials and residents to obtain a comprehensive understanding of the use of the application. Data collection was carried out through observation, interviews, and documentation. The study shows that the Village SIAP application is generally effective in providing budget transparency through accurate and complete budget and realization features, although improvements are still needed in the details and relevance of information, especially in the village planning menu which is considered too general. These findings highlight the advantages and disadvantages of the application while providing recommendations to improve the quality of electronic services. The results of the study are expected to provide practical recommendations that can be applied to improve the quality of service effectiveness of application use in Bojonegoro Regency.